Armored lignin-based articles and methods of making same
"armored" lignin nanoparticles are prepared by mixing lignin with acrylate functional group derivatives of natural oils and polyvinyl alcohol, and preparing products through electrospinning technology, which solves the problem of poor solvent resistance of lignin and achieves the long-term stable performance and versatility of the products.
Patent Information
- Application Number
- CN202510047382.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Lignin has poor solvent resistance in packaging materials and is easily damaged, resulting in a decline in its performance. How to effectively protect lignin so that it can play a role in a long-term and stable manner has become an urgent problem to be solved.
"armored" lignin nanoparticles were prepared by mixing lignin with acrylate functional derivatives of natural oils and polyvinyl alcohol, and products based on "armored" lignin were prepared by electrospinning technology.
The obtained products have excellent ability to block air, moisture and ultraviolet rays, excellent antibacterial and mechanical properties, and are degradable, and can play a stable role in the long term. They are suitable for food preservation, food packaging and tableware packaging.
Smart Images

Figure SMS_1 
Figure HDA0005238929440000011 
Figure HDA0005238929440000012
Abstract
Description
Technical Field
[0001] The invention relates to a product based on "armored" lignin and a preparation method thereof, belonging to the technical field of green food packaging materials. Background Art
[0002] Due to the inherent antibacterial, antioxidant and UV blocking properties of lignin, it has become a material with broad application prospects in the field of environmentally friendly food preservation. At present, lignin is also used in the packaging material industry. However, lignin has poor solvent resistance and is easily damaged, resulting in a decrease in its performance. How to effectively protect lignin so that it can function stably and long-term has become an urgent problem to be solved. Summary of the invention
[0003] Problem that the invention aims to solve
[0004] The purpose of the present invention is to provide a product based on "armored" lignin and a preparation method thereof. The preparation method of the present invention can protect the lignin to a great extent, so that it can function stably for a long time and enhance its other properties to a certain extent. The product based on "armored" lignin thus obtained has excellent air, moisture and ultraviolet barrier capabilities, and also has excellent antibacterial and mechanical properties and is degradable, and can be widely used in food preservation, food packaging, tableware packaging and other fields.
[0005] Solutions for solving problems
[0006] The present inventors conducted intensive research to solve the above-mentioned problems and found that by "armoring" lignin, the armored lignin is more stable and can play the corresponding role for a long time and effectively, thus solving the above-mentioned problems and completing the present invention.
[0007] That is, the present invention is as follows.
[0008] [1]. A method for preparing a product based on "armored" lignin, wherein the preparation method comprises:
[0009] Step A: mixing lignin, acrylate functional derivatives of natural oils and polyvinyl alcohol to obtain "armored" lignin nanoparticles; and
[0010] Step B: preparing an "armored" lignin-based product by electrospinning a spinning solution containing the "armored" lignin nanoparticles.
[0011] [2] The preparation method according to [1], wherein the acrylate functional group derivative of natural oil comprises an acrylate functional group derivative of soybean oil;
[0012] Preferably, the acrylate functional derivative of soybean oil comprises epoxidized soybean oil acrylate.
[0013] [3] The preparation method according to [2], wherein the step A comprises:
[0014] Step A1: mixing a mixture containing an epoxy compound and acrylic acid with at least one selected from the group consisting of a polymerization inhibitor and a catalyst to obtain an acrylate functional group derivative of a natural oil;
[0015] Step A2: Mix lignin, the acrylate functional derivative of the natural oil obtained in step A1, and polyvinyl alcohol to obtain "armored" lignin nanoparticles.
[0016] [4] The preparation method according to [3], wherein step A1 satisfies at least one of the following:
[0017] (a) the ratio of the number of epoxy groups in the epoxy compound to the number of carboxyl groups in the acrylic acid is 1:1 to 1.2:1;
[0018] (b) the epoxidized compound comprises epoxidized soybean oil;
[0019] (c) the polymerization inhibitor is 4-methoxyphenol;
[0020] (d) the catalyst is anthraquinone;
[0021] (e) the mass ratio of the epoxy compound to the acrylic acid is 14:1 to 15:1;
[0022] (f) the mass ratio of the polymerization inhibitor to the epoxy compound is 1:1000 to 1:900;
[0023] (g) the mass ratio of the catalyst to the epoxy compound is 1:77 to 1:78;
[0024] (h) When the acid value of the reactant is lower than 8 mg / g, the reaction is stopped.
[0025] [5] The preparation method according to any one of [1] to [4], wherein in the step A or the step A2, the mass ratio of the lignin to the acrylate functional group derivative of the natural oil is 1:1 to 1:2.
[0026] [6] The preparation method according to any one of [1] to [5], wherein the step B comprises the following steps:
[0027] Step B1: mixing the “armored” lignin nanoparticles, cellulose acetate and an organic solvent to obtain a spinning solution;
[0028] Step B2: preparing an “armored” lignin-based product by electrospinning the spinning solution.
[0029] [7] The preparation method according to [6], wherein the step B1 satisfies at least one of the following:
[0030] (i) the organic solvent comprises acetone and N,N-dimethylformamide;
[0031] (j) the mass of cellulose acetate accounts for 40-45% of the total mass of the spinning solution;
[0032] (k) the mass of acetone accounts for 0.1 to 0.2% of the total mass of the spinning solution;
[0033] (l) N,N-dimethylformamide accounts for 57-60% of the total mass of the spinning solution;
[0034] (m) The “armored” lignin nanoparticles account for 1-2% of the total mass of the spinning solution.
[0035] [8]. The preparation method according to [6], wherein in step B2, the electrospinning conditions are: the volume of the syringe is 10.00 mL, the syringe is equipped with a 1.5 mm needle, the controllable extrusion rate is 1.00 mL / min, and the needle applied voltage is 20.00 kV.
[0036] [9]. A product based on "armored" lignin, wherein the product based on "armored" lignin is obtained according to the preparation method described in any one of [1] to [8].
[0037]
[10] The product according to [9], wherein the armored lignin-based product contains 1 to 3% by mass of armored lignin nanoparticles;
[0038] Preferably, the “armored” lignin nanoparticles include a core portion and a shell portion covering at least a portion of the outer surface of the core portion.
[0039] The core comprises lignin,
[0040] The shell portion comprises an acrylate-functional derivative of a natural oil and polyvinyl alcohol.
[0041] Effects of the Invention
[0042] The preparation method of the present invention can protect lignin to a great extent, so that it can play a role in a long-term and stable manner, while having a certain enhancement effect on its other properties. The products based on "armored" lignin thus obtained have excellent ability to block air, moisture and ultraviolet rays, and also have excellent antibacterial and mechanical properties and are degradable. They can be widely used in food preservation, food packaging, tableware packaging and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1a The preparation mechanism of “armored” lignin nanoparticles is shown.
[0044] Figure 1b The epoxidized soybean oil acrylate (AESO) in Examples 1 to 3 is shown. 1 H NMR spectrum.
[0045] Figure 1c FTIR characterization of the "armored" lignin nanoparticles in Examples 1-3 is shown.
[0046] Figure 2a Scanning electron microscope images of the “armored” lignin nanoparticles prepared in Examples 1 to 3.
[0047] Figure 2b Transmission electron microscope images of the “armored” lignin nanoparticles at different magnifications in Example 1.
[0048] Figure 2c The formation process of the "armored" lignin nanoparticles in Example 1 is shown.
[0049] Figure 2d The size distribution of the "armored" lignin nanoparticles in Examples 1-3 is shown.
[0050] Figure 3a Scanning electron microscope images of the "armored" lignin-based products of Examples 1 to 3 (barrier, degradable, antibacterial food preservative films with an "armored" lignin content of 3%).
[0051] Figure 3b Thermogravimetric analysis of the "armored" lignin based products of Examples 1-3 is shown.
[0052] Figure 3c The elongation and tensile strength of the "armored" lignin based products of Examples 1-3 are shown.
[0053] Figure 3d The visible and ultraviolet light transmittances of the "armored" lignin-based products of Examples 1-3 are shown.
[0054] Figure 3eThe gas separation performance of the "armored" lignin based products of Examples 1-3 is shown.
[0055] Figure 3f The water contact angles of the "armored" lignin-based products of Examples 1-3 are shown.
[0056] Figure 4a The antimicrobial activity of the "armored" lignin-based products of Examples 1 to 3 is shown.
[0057] Figure 4b The practical application of the antioxidant properties of the "armored" lignin-based products of Examples 1 to 3 is shown.
[0058] Figure 4c The natural degradation properties of the "armored" lignin-based products of Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0059] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0060] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0061] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0062] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0063] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0064] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0065] <Method for preparing products based on "armored" lignin>
[0066] In a first aspect of the present invention, there is provided a method for preparing a product based on "armored" lignin, comprising:
[0067] Step A: mixing lignin, acrylate functional derivatives of natural oils and polyvinyl alcohol to obtain "armored" lignin nanoparticles; and
[0068] Step B: The spinning solution containing the above-mentioned "armored" lignin nanoparticles is electrospinned to prepare an "armored" lignin-based product.
[0069] The present invention performs "armored" protection on lignin. The "armored" lignin is more stable and can play a corresponding role for a long time and effectively. The products based on the "armored" lignin thus obtained have excellent ability to block air, moisture and ultraviolet rays, and also have excellent antibacterial and mechanical properties and are degradable. They can be widely used in food preservation, food packaging, tableware packaging and other fields.
[0070] (Process A)
[0071] In step A, lignin, acrylate-functional derivatives of natural oils, and polyvinyl alcohol are mixed to obtain "armored" lignin nanoparticles.
[0072] Lignin is a high molecular weight phenolic compound involved in the lignification of higher plants, also known as lignin. The molecular weight varies depending on the type of biomass, extraction method, and analysis method, but the general number average molecular weight reported is 2,400 to 9,700 (Biofuels Bioproducts & Biorefinering, Volume 8, Issue 6, 836-856 (2014)).
[0073] Lignin may be lignin separated from plants by physical pulverization or chemical decomposition in the process of separating lignin from cellulose and hemicellulose in plants. In addition, it may also include lignin derivatives produced by acetylation, methylation, halogenation, nitration, sulfonation, phenolation of lignin by the solvent or catalyst used in the separation process, or by reaction with sodium sulfide or hydrogen sulfide.
[0074] As a method for separating and extracting lignin from plants, kraft paper method, sulfuric acid method, explosion method, etc. can be cited. Most of the lignin produced in large quantities now is obtained as residue when manufacturing cellulose as a raw material for paper and bioethanol. As the lignin that can be obtained, lignin sulfonate mainly produced by sulfuric acid method can be cited. In addition, there are alkali lignin, organic solvent lignin, solvent decomposition lignin, dioxane lignin and ground wood lignin, explosion lignin, etc. Regardless of the extraction method, the lignin used in the present invention can use the lignin recorded above. As a plant raw material, as long as lignin can be extracted, it is not particularly limited. For example, bamboo, straw, wheat straw, poplar, eucalyptus, acacia, fir, rice straw, wheat straw, cypress, acacia, willow, poplar, bagasse, corn, sugarcane, cereals, eucalyptus, sugarcane grass, etc. can be cited. As lignin, commercial products can also be used.
[0075] In some preferred embodiments, the lignin preferably comprises at least one of alkali lignin, lignin sulfonate, organic solvent pulping lignin, or lignin separated and prepared from bamboo, straw, wheat straw, poplar, eucalyptus or acacia.
[0076] Alkali lignin can be prepared from black liquor obtained by cooking wood chips with caustic soda (NaOH). During cooking, the liquid ratio of wood chips to cooking liquor can be set to, for example, 1.0 to 40 L / g.
[0077] In the above-mentioned alkali cooking, in addition to caustic soda (NaOH), various cooking aids may be used in combination. For example, 0.01 to 5% by mass of quinone may be added per unit of absolute dry crumbs.
[0078] The quinones used are quinone compounds, hydroquinone compounds or their precursors which are so-called well-known cooking aids, and at least one compound selected from these substances can be used. Examples of these compounds include anthraquinone, dihydroanthraquinone, tetrahydroanthraquinone, methylanthraquinone, sugar compounds or their precursors.
[0079] The obtained cooking liquor can be used directly as alkali lignin, or a product obtained by purifying lignin from the obtained cooking liquor can be used as alkali lignin. Powdered alkali lignin obtained by spray-drying and powdering an alkaline solution of alkali lignin (or the obtained cooking liquor) or acid-precipitated alkali lignin obtained by precipitating an alkaline solution of alkali lignin with an acid can be used.
[0080] In some preferred embodiments, the lignin may not require further purification.
[0081] As the lignin sulfonate, sodium salt, potassium salt, calcium salt, magnesium salt, ammonium salt or 1 to 4 substituted ammonium salts are preferred. Specific examples include sodium lignin sulfonate, potassium lignin sulfonate, calcium lignin sulfonate, magnesium lignin sulfonate, ammonium lignin sulfonate, etc. The lignin sulfonate may be a commercially available product.
[0082] The lignin used in the present invention may be in powder form or in liquid form, preferably in powder form. Liquid lignin may be prepared by dissolving the powdered lignin in a suitable solvent (e.g., water, sodium hydroxide solution, etc.) to form liquid lignin.
[0083] "Acrylate functional derivatives of natural oils" can be prepared by addition reaction of an oil component having a functional group with acrylic acid or a functional derivative of acrylic acid. In some embodiments, the oil is an unsaturated oil that is epoxidized and then esterified with acrylic acid to provide oil acrylates.
[0084] Examples of the natural oil include at least one of soybean oil, linseed oil, tung oil, coconut oil, corn oil, cottonseed oil, olive oil, palm oil, palm kernel oil, and peanut oil.
[0085] In some preferred embodiments, the acrylate-functional derivative of a natural oil comprises an acrylate-functional derivative of soybean oil.
[0086] In some preferred embodiments, the acrylate functional derivative of soybean oil comprises epoxidized soybean oil acrylate. In this preferred embodiment, epoxidized soybean oil is reacted with acrylic acid to provide β-hydroxy acrylate to obtain epoxidized soybean oil acrylate.
[0087] In some preferred embodiments, step A further comprises:
[0088] Step A1: mixing a mixture containing an epoxy compound and acrylic acid with at least one selected from the group consisting of a polymerization inhibitor and a catalyst to obtain an acrylate functional group derivative of a natural oil;
[0089] Step A2: Mix lignin, the acrylate functional derivative of the natural oil obtained in the above step A1, and polyvinyl alcohol to obtain "armored" lignin nanoparticles.
[0090] In step A1, the ratio of the number of epoxy groups in the epoxy compound to the number of carboxyl groups in acrylic acid is preferably 1:1 to 1.2:1. In some specific embodiments, the ratio of the number of epoxy groups in the epoxy compound to the number of carboxyl groups in acrylic acid is 1:1, 1.1:1 or 1.2:1.
[0091] As the epoxy compound, epoxidized soybean oil is preferably contained.
[0092] As the polymerization inhibitor, 4-methoxyphenol is preferred.
[0093] The catalyst is preferably anthraquinone.
[0094] Epoxides, acrylic acids, polymerization inhibitors, and catalysts are commercially available.
[0095] In some preferred embodiments, the mass ratio of epoxy compound to acrylic acid is 14: 1 to 15: 1. In some specific embodiments, the mass ratio of epoxy compound to acrylic acid is 14: 1, 14.2: 1, 14.5: 1, 14.8: 1 or 15: 1.
[0096] In some preferred embodiments, the mass ratio of the polymerization inhibitor to the epoxy compound is 1:1000 to 1:900. In some specific embodiments, the mass ratio of the polymerization inhibitor to the epoxy compound is 1:1000, 1:980, 1:950, 1:920 or 1:900.
[0097] In some preferred embodiments, the mass ratio of the catalyst to the epoxy compound is 1:77 to 1:78.
[0098] In the present invention, by setting the amounts of the epoxy compound, acrylic acid, the polymerization inhibitor, and the catalyst within the above ranges, an acrylate functional group derivative of a natural oil can be obtained efficiently and satisfactorily.
[0099] In step A1, the reaction is stopped when the acid value of the reactant is lower than 8 mg / g. The acid value is measured using a fully automatic acid value measuring instrument.
[0100] In some preferred embodiments, step A1 preferably includes the following steps:
[0101] Step a1: epoxidized soybean oil, acrylic acid and polymerization inhibitor were mixed and stirred at room temperature for 10 minutes at a stirring speed of 300 r / min;
[0102] Step a2: Add the catalyst to the mixture obtained in the above step a1, stir at a speed of 300 r / min and raise the temperature to 80°C. After 30 minutes, further raise the temperature to 120°C, measure the acid value of the reactant, and stop the reaction when the acid value is lower than 8 mg / g.
[0103] In the above steps A and A2, the mass ratio of lignin to the acrylate functional derivative of natural oil is 1:1 to 1:2. In some specific embodiments, the mass ratio of lignin to the acrylate functional derivative of natural oil is 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2. By setting the mass ratio of lignin to the acrylate functional derivative of natural oil within the above range, "armored" lignin nanoparticles can be obtained efficiently and well.
[0104] In step A, it is preferred that a mixture containing lignin, an acrylate functional derivative of a natural oil, and polyvinyl alcohol is mixed with at least one selected from the group consisting of butyl acetate and azobisisobutyronitrile.
[0105] In some preferred embodiments, the mass ratio of butyl acetate to lignin is 17.9:1 to 18.1:1, the added mass of azobisisobutyronitrile is 1.9 to 2.1% of the added mass of lignin, and the added mass of polyvinyl alcohol (PVA) / water mixed solution is 17.1 to 18.9% of the added mass of lignin. By setting the amount of butyl acetate, azobisisobutyronitrile and PVA / water mixed solution to the above range, "armored" lignin nanoparticles can be obtained efficiently and well.
[0106] In some preferred embodiments, step A or step A2 comprises a multi-stage stirring step, and the multi-stage stirring step comprises the following steps:
[0107] A first stirring step, stirring a mixture of lignin, an acrylate functional derivative of a natural oil, a polyvinyl alcohol / water mixed solution, and at least one selected from the group consisting of butyl acetate and azobisisobutyronitrile at room temperature (23 to 25° C.) at a first stirring speed, wherein the first stirring speed is preferably 1200 to 1500 r / min;
[0108] A second stirring step, sealing the mixture obtained in the first stirring step and stirring it at a temperature of 70° C. at a second stirring speed of 900 r / min;
[0109] In the third stirring step, the mixture obtained in the second stirring step was stirred in an open air environment (at 23 to 25° C.) at a third stirring speed, and the third stirring speed was 900 r / min.
[0110] In order to better obtain "armored" lignin nanoparticles, the first stirring speed in the first stirring step is preferably maintained for 1 to 2 hours, the second stirring speed in the second stirring step is preferably maintained for 24 hours, and the third stirring speed in the third stirring step is preferably maintained for 24 hours.
[0111] In some preferred embodiments, step A further comprises: after step A2, washing and / or separating the above-obtained substance.
[0112] There is no particular limitation on the specific method of washing, for example, deionized water can be used for washing. The number of washing times can be, for example, more than one time, preferably five times.
[0113] There is no particular limitation on the specific method of separation, for example, separation can be performed by centrifugation. For centrifugation, for example, a horizontal or butterfly centrifuge can be used for separation. In some preferred embodiments, a centrifuge is used to centrifuge at 8500-9000 r / min for 10-15 min.
[0114] Figure 1a The preparation mechanism of “armored” lignin nanoparticles is shown. Figure 1a As shown, the "armored" lignin nanoparticles of the present invention include a core and a shell covering at least a portion of the outer surface of the core, thereby obtaining an "armored" lignin nanoparticle with a lignin core and a surface-coated acrylate functional group derivative of a natural oil (e.g., epoxidized soybean oil acrylate (AESO)) and polyvinyl alcohol (PVA). Here, the shell can cover the entire outer surface of the core.
[0115] The core portion comprises lignin, and the shell portion comprises an acrylate functional group derivative of a natural oil (e.g., epoxidized soybean oil acrylate (AESO)) and polyvinyl alcohol (PVA). The core portion and the shell portion are connected by a carboxyl group generated by a ring-opening reaction between the hydroxyl group of lignin and the epoxidized soybean oil acrylate.
[0116] (Process B)
[0117] In step B, the spinning solution containing the above-mentioned "armored" lignin nanoparticles is electrospinned to prepare an "armored" lignin-based product.
[0118] In some preferred embodiments, step B preferably includes the following steps:
[0119] Step B1: mixing the above-mentioned “armored” lignin nanoparticles, cellulose acetate and an organic solvent to obtain a spinning solution;
[0120] Step B2: The above spinning solution is subjected to electrostatic spinning to prepare a product based on “armored” lignin.
[0121] [Process B1]
[0122] Examples of the organic solvent include acetone and / or N,N-dimethylformamide.
[0123] In some preferred embodiments, cellulose acetate and an organic solvent are preferably first mixed under high-speed stirring at 500 r / min until completely dissolved, and then the "armored" lignin nanoparticles are added and stirred until completely dissolved.
[0124] In some preferred embodiments, the mass of cellulose acetate accounts for 40% to 45% of the total mass of the spinning solution; the mass of acetone accounts for 0.1% to 0.2% of the total mass of the spinning solution; N,N-dimethylformamide accounts for 57% to 60% of the total mass of the spinning solution; and the "armored" lignin nanoparticles account for 1% to 2% of the total mass of the spinning solution.
[0125] In some specific embodiments, the mass of cellulose acetate accounts for 40%, 41%, 42%, 43%, 44% or 45% of the total mass of the spinning solution; the mass of acetone accounts for 0.1%, 0.12%, 0.14%, 0.16%, 0.18% or 0.2% of the total mass of the spinning solution; N,N-dimethylformamide accounts for 57%, 58%, 59% or 60% of the total mass of the spinning solution; and the "armored" lignin nanoparticles account for 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2% of the total mass of the spinning solution.
[0126] [Process B2]
[0127] In some preferred embodiments, the spinning solution is preferably transferred to a syringe and extruded at a controllable rate using a syringe pump while applying a suitable voltage to the needle. The nanofibers prepared by the electrospinning technique are collected on a drum receiver covered with aluminum foil, and a product based on "armored" lignin is obtained after drying.
[0128] In some preferred embodiments, the volume of the syringe is 10.00 mL, the syringe is equipped with a 1.5 mm needle, the controllable extrusion rate is 1.00 mL / min, and the voltage applied to the needle is 20.00 kV.
[0129] In some preferred embodiments, the drying temperature is 80° C. and the drying time is 2 h.
[0130] According to the preparation method of the present invention, a product based on "armored" lignin with an "armored" lignin content of 1 to 3% by mass can be obtained. The present invention "armored" lignin protects the lignin, and the "armored" lignin is more stable and can play a corresponding role for a long time and effectively. The product based on "armored" lignin obtained has excellent air, moisture and ultraviolet barrier capabilities, and has excellent antibacterial and mechanical properties and is degradable, and can be widely used in food preservation, food packaging, tableware packaging and other fields.
[0131] <Products based on “armored” lignin>
[0132] In the second aspect of the present invention, a product based on "armored" lignin is provided. The product based on "armored" lignin is obtained according to the preparation method described in the first aspect.
[0133] In some preferred embodiments, the "armored" lignin-based product comprises 1 to 3% by mass of "armored" lignin nanoparticles.
[0134] In some preferred embodiments, the "armored" lignin nanoparticles of the present invention include a core and a shell covering at least a portion of the outer surface of the core, thereby obtaining "armored" lignin nanoparticles with a lignin core and a surface coated with epoxidized soybean oil acrylate (AESO) and polyvinyl alcohol (PVA). Here, the shell can cover the entire outer surface of the core.
[0135] The core part comprises lignin, and the shell part comprises epoxidized soybean oil acrylate (AESO) and polyvinyl alcohol (PVA). The core part and the shell part are connected by carboxyl groups generated by ring-opening reaction between hydroxyl groups of lignin and epoxidized soybean oil acrylate.
[0136] Example
[0137] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0138] Example 1
[0139] (1) Preparation of epoxidized soybean oil acrylate (AESO)
[0140] 60.00g of epoxidized soybean oil (ESO) and 4.10g of acrylic acid (AA) were mixed so that the ratio of the number of epoxy groups to carboxyl groups was maintained at 1.12:1. Subsequently, 0.06g of 4-methoxyphenol was added to the mixture and stirred at room temperature for 10min (300r / min). Then, 0.77g of anthraquinone was slowly added to the above mixture, and the temperature was raised to 80°C while stirring. After 30min, the temperature was further raised to 120°C (300r / min). The acid value of the reactants was measured regularly using a fully automatic acid value tester, and the reaction was stopped when the acid value was lower than 8mg / g. The product was first poured into butanone, and then poured into ether for precipitation after complete dissolution. The precipitate was collected and the unreacted sample was removed to obtain the product epoxidized soybean oil acrylate (AESO).
[0141] (2) Preparation of “armored” lignin nanoparticles
[0142] A mixture of 0.50 g of lignin (OL, residual lignin from enzymatic hydrolysis of corn cobs manufactured by Shandong Longli Biotechnology Co., Ltd.), 0.50 g of AESO prepared by the above step (1), 9.00 g of butyl acetate and 10.00 mg of azobisisobutyronitrile was gradually added dropwise to 90.00 mL of a PVA / water mixed solution (1 wt%), while vigorously stirring at a speed of 1500 r / min for 1 h. The above mixture was then sealed and stirred at a speed of 900 r / min at a temperature of 70°C. After 24 h, the sealing ring was removed, and the mixture was then stirred for another 24 h at a speed of 900 r / min in an open air environment. The final product was washed with deionized water and centrifuged at a speed of 9000 r / min. Repeated 5 times to obtain the product "armored" lignin nanoparticles (AS-OL NPs).
[0143] (3) Preparation of barrier biodegradable antibacterial food wrap with 3% armored lignin content
[0144] 2.00g of cellulose acetate, 7.00mg of acetone and 3.00mL of N,N-dimethylformamide were placed in a three-necked flask and mixed, and stirred at a high speed of 500r / min until completely dissolved. Then 60.00mg of the "armored" lignin nanoparticles prepared by the above step (2) were added to the flask and stirred. After complete dissolution, a spinning solution for electrospinning was obtained. The above spinning solution was transferred to a 10.00mL syringe (equipped with a 1.5mm needle), and extruded at a controllable rate (1.00mL / min) using a syringe pump, while applying a voltage of 20.00kV to the needle. The nanofibers prepared by electrospinning technology were collected on a drum receiver covered with aluminum foil, and dried at 80°C for 2h to obtain a barrier degradable antibacterial food preservative film with an "armored" lignin content of 3%.
[0145] Example 2
[0146] The preparation was carried out in the same manner as in Example 1 except that the lignin in the preparation of the above-mentioned (2) "armored" lignin nanoparticles was changed to lignin (DL, the product of CuMnO2 nanoenzyme degrading OL lignin, the molecular weight of DL is higher than EL).
[0147] The “armored” lignin nanoparticles prepared in this example are denoted as “AS-DL NPs”.
[0148] Example 3
[0149] The preparation was carried out in the same manner as in Example 1, except that the lignin in the preparation of the above (2) "armored" lignin nanoparticles was changed to lignin (EL, the product of CuMnO2 nanoenzyme degradation of OL lignin).
[0150] The “armored” lignin nanoparticles prepared in this example are denoted as “AS-EL NPs”.
[0151] Figure 1b The epoxidized soybean oil acrylate (AESO) in Examples 1 to 3 is shown. 1 H NMR spectrum: 1 H NMR (600MHz, CDCl3, TMS, δ): 5.26 (s, 3H, OH), 4.15-4.29 (m, 6H, CHOCH), 2.89-3.11 (m, 9H, C H2=CH), 2.31(t,3H,CHOH), 1.74(m,3H,CHO), 1.25-1.60(m,76H,CH2CH2), 0.88(t,9H,CH3).
[0152] Figure 1c The FTIR characterization of the “armored” lignin nanoparticles in Examples 1 to 3 is shown: the characteristic peak of the epoxy group is located at 1743 cm -1 The -OH peak is located at 3400 cm -1 and 3450cm -1 The -CH3 and -CH2- peaks are located at 2900 cm -1 and -2800cm -1 The COC peak is located at 1110 cm -1 1600cm -1 、1512cm -1 and 1454cm -1 The peak at can be attributed to the stretching of the aromatic ring of the phenylpropane skeleton of lignin.
[0153] exist Figure 1c In the table, "AS-OL NPs", "AS-DL NPs" and "AS-EL NPs" all represent "armored" lignin nanoparticles. AS is the abbreviation of epoxidized soybean oil acrylate, OL, DL and EL represent lignin from different sources (OL represents residual lignin from corn cobs hydrolyzed by enzymes manufactured by Shandong Longli Biotechnology Co., Ltd., and DL and EL represent products of degradation of OL lignin by nanozyme CuMnO2), and NPs indicates that the final "armored" lignin nanoparticles are nanoscale products.
[0154] Figure 2aThe scanning electron microscope images of the "armored" lignin nanoparticles prepared in Examples 1 to 3. It can be observed from the SEM images that the "armored" lignin nanoparticles are uniform in size and well dispersed.
[0155] Figure 2b The transmission electron microscope images of the "armored" lignin nanoparticles at different magnifications in Example 1. It can be observed from the TEM image that the "armored" lignin nanoparticles present a double-layer structure, the darker inner part is composed of lignin, and the lighter outer part is composed of AESO and PVA.
[0156] Figure 2c The formation process of the “armored” lignin nanoparticles in Example 1 is shown, which ultimately leads to the generation of “armored” lignin nanoparticles through a series of continuous thermally induced electron transfer, proton release, and subsequent free radical coupling.
[0157] Figure 2d The size distribution of the "armored" lignin nanoparticles in Examples 1 to 3 is shown. The size distribution of the "armored" lignin nanoparticles prepared in Examples 1 to 3 is uniform.
[0158] exist Figure 2d In the table, "AS-OL NPs", "AS-DL NPs" and "AS-EL NPs" all represent "armored" lignin nanoparticles. AS is the abbreviation of epoxidized soybean oil acrylate, OL, DL and EL represent lignin from different sources (OL represents residual lignin from corn cobs hydrolyzed by enzymes manufactured by Shandong Longli Biotechnology Co., Ltd., and DL and EL represent products of degradation of OL lignin by nanozyme CuMnO2), and NPs indicates that the final "armored" lignin nanoparticles are nanoscale products.
[0159] Figure 3a The scanning electron microscope images of the "armored" lignin-based products (barrier, degradable, antibacterial food cling film with a "armored" lignin content of 3%) of Examples 1 to 3. It can be observed from the SEM images that the nanofibers constituting the "armored" lignin-based products with a "armored" lignin content of 3% are uniformly distributed in size and have no beads.
[0160] Figure 3b Thermogravimetric analysis of the "armored" lignin-based products of Examples 1 to 3 is shown. From this figure, it can be seen that the "armored" lignin-based products of Examples 1 to 3 have excellent thermal stability.
[0161] Figure 3c The elongation and tensile strength of the "armored" lignin-based products of Examples 1 to 3 are shown. From this figure, it can be seen that the "armored" lignin-based products of Examples 1 to 3 have excellent mechanical properties.
[0162] Figure 3d The transmittance of visible light and ultraviolet light of the "armored" lignin-based products of Examples 1 to 3 is shown. From the figure, it can be seen that the "armored" lignin-based products of Examples 1 to 3 have excellent natural light and ultraviolet light shielding properties.
[0163] Figure 3e The gas separation performance of the "armored" lignin-based products of Examples 1 to 3 is shown. As can be seen from the figure, the "armored" lignin-based products of Examples 1 to 3 have excellent gas barrier properties.
[0164] Figure 3f The water contact angles of the "armored" lignin-based products of Examples 1 to 3 are shown. From the figure, it can be seen that the "armored" lignin-based products of Examples 1 to 3 have excellent water molecule isolation performance.
[0165] exist Figure 3a~3f In the reference numerals, “CA” indicates a cellulose acetate film.
[0166] Figure 4a The antimicrobial activity of the "armored" lignin-based products of Examples 1 to 3 is shown. As can be seen from the figure, the "armored" lignin-based products of Examples 1 to 3 have excellent antimicrobial properties.
[0167] Figure 4b The figure shows the practical application of the antioxidant properties of the "armored" lignin-based products of Examples 1 to 3. As can be seen from the figure, the "armored" lignin-based products of Examples 1 to 3 have excellent antioxidant practical application effects.
[0168] Figure 4c The figure shows the natural degradation performance of the "armored" lignin-based products of Examples 1 to 3. As can be seen from the figure, the "armored" lignin-based products of Examples 1 to 3 have excellent natural degradation performance.
[0169] After 2 weeks, the degradation rate of the CA film was 15.7%, the degradation rate of the "armored" lignin-based product (AS-OLNPs / CA) prepared in Example 1 was 19.6%, the degradation rate of the "armored" lignin-based product (AS-DL NPs / CA) prepared in Example 2 was 17.9%, and the degradation rate of the "armored" lignin-based product (AS-EL NPs / CA) prepared in Example 3 was 19.8%.
[0170] exist Figures 4a to 4c In the table, “Blank” indicates a control, and fresh apple pieces were used as a control. “CA” indicates cellulose acetate membrane.
[0171] <Evaluation Test>
[0172] (1) Epoxidized soybean oil acrylate (AESO) 1 H NMR spectroscopy:
[0173] Dissolve 5 mg of sample in 0.5 mL CDCl3-d, and place the NMR tube containing CDCl3-d solution into a Rucker AVAVCEIII HD 700 MHz spectrometer for measurement at a temperature of 25°C. Figure 1b )
[0174] (2) Measurement of infrared spectra of “armored” lignin nanoparticles:
[0175] KBr and sample ("armored" lignin nanoparticles) are mixed in an appropriate ratio to prepare a uniform mixture, and then pressed into a sheet under high pressure. Carefully take out the sample sheet, place it on a magnetic sample holder, and put it into the sample chamber of the intelligent Fourier transform infrared spectrometer. The measurement is carried out under the selected instrument program. Usually, the blank background of KBr is measured first, and then the sample is placed in the light path to measure the sample infrared spectrum (400-4000cm -1 ). Figure 1c )
[0176] (3) Sample morphology analysis:
[0177] Scanning electron microscopy (SEM, Jeol JSM-7800F, Japan) was used to examine the sample morphology.
[0178] Take a sample of appropriate size, stick it on the sample table, and after gold spraying, place it in the test chamber and evacuate it for observation. The acceleration voltage is 5 to 15 kV. Figure 2a , Figure 3a )
[0179] (4) Analysis of fine structure morphology inside the sample:
[0180] Transmission electron microscopy (TEM, JEM-2100 (UHR)) was used to examine the fine structure morphology of the samples.
[0181] Take appropriate amount of powder and ethanol and add them to a small beaker, perform ultrasonic oscillation for 10 to 30 minutes, and after 3 to 5 minutes, use a glass capillary to absorb the uniform mixture of powder and ethanol, and then drop 2 to 3 drops of the mixed liquid onto the microgrid, and wait for more than 15 minutes to allow the ethanol to evaporate as much as possible. The sample is placed in the detection chamber and evacuated for observation, with an acceleration voltage of 5 to 15 kV. ( Figure 2b )
[0182] (5) Particle size determination:
[0183] The particle size was measured using a dynamic light scattering technique using a nanoparticle size and zeta potential analyzer (Opptronix-929SZ). Figure 2d )
[0184] (6) Thermal stability analysis:
[0185] The thermal stability of the samples was tested by a thermogravimetric analyzer (TGA, TAQ50, USA). 5-10 mg of the sample was weighed and placed flat on a platinum test plate. In a nitrogen atmosphere (flow rate 40 mL / min), it was heated from room temperature to 700°C at a rate of 10°C / min. Figure 3b )
[0186] (7) Mechanical properties test:
[0187] The tensile strength of nanofibers was tested using a universal testing machine (Shimadze AGS-X, Japan). The nanofiber felt was cut into 1×5 cm sample strips. To prevent the sample from breaking at the clamping point during the test, 2×2 cm cardboard was glued to both ends of the sample strip with quick-drying glue. The clamp was clamped on the cardboard for testing. The effective test length was 3 cm. A 50N sensor was loaded, the test rate was 2 mm / min, and 10 samples were tested in each group to calculate the average value. ( Figure 3c )
[0188] (8) Anti-ultraviolet performance test:
[0189] All samples were wrapped on the surface of paper tape for UV transmittance measurement (at least three samples were prepared for each UV transmittance measurement). The samples were placed in the dark. The UV transmittance of the samples was measured using a Cary100 spectrophotometer (Agilent Technologies, USA). Each sample was scanned at 3-5 points. For each scan, the transmittance (T) measurements were collected in the wavelength range from UVB (290-320 nm) to UVA (320-400 nm). ( Figure 3d )
[0190] (9) O2 gas permeation test:
[0191] The differential pressure gas transmission instrument (GTR TEC-GTR-11MH, Kyoto, Japan; test area: 0.785 cm 2 ) for measurement. The instrument test temperature is 34°C, the test pressure is maintained at 49KPa, and the test pressure is 0.1MPa. The carrier gas is H2, and the pressure is 0.5MPa. The sample is placed at the air inlet, and the timing starts when the gas is detected passing through. The gas permeation of the membrane is measured after 2 hours. ( Figure 3e )
[0192] (10) Contact angle test:
[0193] Place the solid sample on the sample stage of the fully automatic contact angle tester (Dynetech-scd-350) and drop the test liquid on the solid sample. The image of the droplet can be recorded by a camera, and the contact angle of the droplet on the solid surface can be analyzed by fitting the contour of the droplet in the analysis software. Figure 3f )
[0194] (11) Antibacterial performance test: Figure 4a )
[0195] Bacterial culture: The antibacterial activity of the tested fiber membranes was detected by colony forming unit (CFU) counting method. Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus were cultured in Luria-Bertani (LB) medium (10 g / L tryptone, 5.0 g / L yeast extract and 10 g / L sodium chloride, pH 7.0).
[0196] Preparation of LB agar plates: Add 1.5% (w / v) agar to LB medium. Inoculate a colony into LB medium and culture at 37°C for 12-16 hours.
[0197] Antibacterial performance test: The culture (1:50, v / v) and the fiber membrane to be tested (4×4 cm 2 ) was added to 5 mL of LB medium. After culturing at 37°C for 2 h, the culture was diluted with fresh sterilized medium, and then 200 μL of the suspension was dropped on an LB agar plate, cultured overnight at 37°C, and CFU was counted the next day. Each experiment was repeated three times, and the total number of bacterial colonies contained in the original sample was calculated based on the dilution factor.
[0198] (12) Freshness preservation performance test:
[0199] Cut the selected fresh apples into 1cm pieces 3 These cubes were placed in a plastic petri dish. Then, the prepared fiber membrane was covered on the surface of the plastic petri dish. Finally, it was kept at room temperature for 3 days and photographed regularly. Fresh apple cubes were used as a control. ( Figure 4b )
[0200] (13) Natural degradation performance test:
[0201] The prepared fiber membrane was cut into pieces of about 3×3 cm 2 , buried under natural soil at a depth of about 4 cm. After 1 week and 2 weeks, the degraded samples and fragments were taken out, the residual soil was gently washed off with distilled water, and then dried at 37°C until a constant weight was obtained. Finally, the weight of the dried sample was weighed again, and the weight loss of the degraded film in the soil was calculated. The degradation rate was calculated according to the following formula. ( Figure 4c )
[0202]
[0203] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0204] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing a product based on "armored" lignin, characterized in that: The preparation method comprises: Step A: mixing lignin, acrylate functional derivatives of natural oils and polyvinyl alcohol to obtain "armored" lignin nanoparticles; and Step B: preparing an "armored" lignin-based product by electrospinning a spinning solution containing the "armored" lignin nanoparticles.
2. The preparation method according to claim 1, characterized in that: The acrylate functional group derivative of the natural oil includes an acrylate functional group derivative of soybean oil; Preferably, the acrylate functional derivative of soybean oil comprises epoxidized soybean oil acrylate.
3. The preparation method according to claim 2, characterized in that: The process A comprises: Step A1: mixing a mixture containing an epoxy compound and acrylic acid with at least one selected from the group consisting of a polymerization inhibitor and a catalyst to obtain an acrylate functional group derivative of a natural oil; Step A2: Mix lignin, the acrylate functional derivative of the natural oil obtained in step A1, and polyvinyl alcohol to obtain "armored" lignin nanoparticles.
4. The preparation method according to claim 3, characterized in that: The step A1 satisfies at least one of the following: (a) the ratio of the number of epoxy groups in the epoxy compound to the number of carboxyl groups in the acrylic acid is 1:1 to 1.2:1; (b) the epoxidized compound comprises epoxidized soybean oil; (c) the polymerization inhibitor is 4-methoxyphenol; (d) the catalyst is anthraquinone; (e) the mass ratio of the epoxy compound to the acrylic acid is 14:1 to 15:1; (f) the mass ratio of the polymerization inhibitor to the epoxy compound is 1:1000 to 1:900; (g) the mass ratio of the catalyst to the epoxy compound is 1:77 to 1:78; (h) When the acid value of the reactant is lower than 8 mg / g, the reaction is stopped.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step A or the step A2, the mass ratio of the lignin to the acrylate functional group derivative of the natural oil is 1:1 to 1:
2.
6. The preparation method according to any one of claims 1 to 5, characterized in that The process B comprises the following steps: Step B1: mixing the "armored" lignin nanoparticles, cellulose acetate and an organic solvent to obtain a spinning solution; Step B2: preparing an armored lignin-based product by electrospinning the spinning solution.
7. The preparation method according to claim 6, characterized in that: The process B1 satisfies at least one of the following: (i) the organic solvent comprises acetone and N,N-dimethylformamide; (j) the mass of cellulose acetate accounts for 40-45% of the total mass of the spinning solution; (k) the mass of acetone accounts for 0.1 to 0.2% of the total mass of the spinning solution; (l) N,N-dimethylformamide accounts for 57-60% of the total mass of the spinning solution; (m) The "armored" lignin nanoparticles account for 1-2% of the overall mass of the spinning solution.
8. The preparation method according to claim 6, characterized in that: In the step B2, the electrospinning conditions are as follows: the volume of the syringe is 10.00 mL, the syringe is equipped with a 1.5 mm needle, the controllable extrusion rate is 1.00 mL / min, and the needle applied voltage is 20.00 kV.
9. A product based on "armored" lignin, characterized in that The "armored" lignin-based product is obtained according to the preparation method according to any one of claims 1 to 8.
10. The product according to claim 9, characterized in that The "armored" lignin-based product contains 1 to 3% by mass of "armored" lignin nanoparticles; Preferably, the "armored" lignin nanoparticles include a core portion and a shell portion covering at least a portion of the outer surface of the core portion. The core comprises lignin, The shell portion comprises an acrylate-functional derivative of a natural oil and polyvinyl alcohol.
Citation Information
Patent Citations
Lignin base skin core structure nanometer / micron fiber and preparation method thereof
CN102517689A
Preparation method of lignin-based electrostatic blended materials
CN104120507A
Preparation method of photo-crosslinked PVA (polyvinyl alcohol) / lignin composite membrane
CN104497341A
Lignin micro-nanosphere / PVA (polyvinyl alcohol) composite membrane material as well as preparation method and application thereof
CN116355251A
Preparation method of walnut shell lignin enhanced polyvinyl alcohol food preservative film
CN118580533A